French Cross-Border Acquisitions : Why Choose Finland? - Helle, Maria (fi=Turun yliopisto|en=University of Turku|, 2017)
While part of the Europe, Finland is a little isolated geographically from the other countries. The institutional environment is rather regulated, labor costs not very low, taxation high and so on. On the other hand, Finland is one of the least corrupted countries in the world and the Finnish straightforward culture is often appreciated in a professional setting. Judging from these aspects, Finland is not the most obviously attractive market to enter for a French company, and there are indeed clearly less French companies present in Finland than in the neighbor country Sweden. And even though France is an important European country in terms of cross-border acquisition amounts, and would be expected to have companies expanding also to Finland, they are still surprisingly few. The objective of this thesis was to find out why those rather rare French companies, that have decided to come to Finland, have made this decision, in other words the study their market entry motives. Acquisition as entry mode was chosen as the focus of this research because it can be considered a significant and thus rather permanent investment for the internationalizing investing party. Dunning’s Eclectic OLI Paradigm was used a theoretical framework to study this phenomenon, combined with the CSA/FSA matrix of the Internalization theory. The chosen method was a qualitative research in the form of a case study. Expert interviews were held to gain a deeper understanding of two example cases of acquisition of Finnish companies by French companies. Both cases fit the market seeking motive type. The acquiring French companies were not specifically interested in the Finnish market, but they saw Finland rather as one of the Nordic countries and as part of Europe. This was the main location advantage. Lyreco, a globally operating company, wanted to be present in also this part of Europe. Mediamobile on the other hand was looking to start their internationalization, and the acquisition allowed them to go from 1 to 6 countries at once. Both companies valued the strong internalization advantages of their acquisitions, which were mostly intangible assets related to their position in the market. The strong ownership advantages of the acquirers, both of them strong players in their fields, allowed them to be chosen by the targets as investors. The findings suggest that French companies should value Finland as a good alternative to the Scandinavian countries for being present in the Nordics. Both Finnish companies were also found to have some interesting corporate culture traits, practices or business topics that the French companies didn’t know of at the time of the acquisition decision, which should thus have been advertised better.